Procedimiento para el cálculo de circuitos en el modelado del flujo en intercambiadores de calor de aletas y tubos (2014)
This paper presents a general method for simulating the flow behavior in the fin-and-tube heat exchangers with high flexibility in handling the information -- This procedure is based on the use of Object-Oriented Programming and specifically using C++, this because of all the advantages of this type of programming -- Data entry is carried out by files, so that third-party programs can generate configuration and permit calculation in parametric form -- The results for the analysis are presented in three different formats: comma separated value (CSV), structured plain text and self-documenting (XML) and a graphical display of results (VTK)